Towards scalable fabrication of ultrasmooth and porous thin carbon films. (January 2016) - Peng, Yucheng; Burtovyy, Ruslan; Yang, Ying; Urban, Marek W.; Kennedy, Marian S.; Kornev, Konstantin G.; Bordia, Rajendra; Luzinov, Igor
Abstract: In this study, we demonstrated that carbon films with nanoscale roughness and controllable thickness can be produced by high temperature treatment of the polyacrylonitrile (PAN) film fabricated through dip-coating from 1, 1, 1, 3, 3, 3-hexafluoro-2-propanol (HFIP) solution. Specifically, ultrasmooth (root mean squared average roughness between 1 and 3 nm), crack-free carbon films were produced. In our procedure, the PAN films were first deposited onto a silicon wafer by conventional dip-coating process. Next, the films were stabilized at 230 °C in air and then carbonized at 1000 °C in an inert atmosphere. Raman spectroscopy indicated that after carbonization the films with ordered graphite structure as well as disordered phase were obtained. The same basic procedure was used to form porous carbon films with tunable porous structures when PAN and polyethylene oxide (PEO) blend was used instead of PAN only. In PAN/PEO blended films, PEO functioned as the pore initiation agent and resulted in carbon films whose pore diameter could be varied from hundreds of nanometers to micrometers. The carbon films (solid and porous) obtained in this study exhibit relatively high electrical conductivity. We expect that the method reported here can be employed for scalable manufacturing of ultrasmooth as well as porous carbon films.